TRANSFORMASI ADMINISTRASI PENDIDIKAN INKLUSIF BAGI PESERTA DIDIK BERKEBUTUHAN KHUSUS DI ERA PENDIDIKAN MODERN: ( Studi Kasus di SDN 1 Ciwareng Kabupaten Purwakarta ) - Tutty R Rossa, Ade; Ruhiat, Asep; Sukmawaty, Siska; Iskandar, Iin; Setiawati, Ina (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the transformation of educational administration in supporting an inclusive education system for Students with Special Needs (SSN) in the modern educational era, with the research conducted at SDN 1 Ciwareng, Purwakarta Regency. The development of the digital era and the concept of Society 5.0 require educational administration governance to transform from conventional systems into adaptive, flexible, collaborative, and technology-based systems in order to ensure the fulfillment of equitable and inclusive educational rights for all students. This study employed a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, field observations, and documentation studies concerning the implementation of educational administration practices at the school. The findings indicate that the transformation of educational administration at SDN 1 Ciwareng was manifested through several main aspects: (1) the digitalization of inclusive student management through the integration of technology-based administrative data systems; (2) the flexibility of adaptive curriculum administration through the implementation of Individualized Education Programs (IEP) tailored to the characteristics and needs of Students with Special Needs; and (3) the transformation of the school’s internal bureaucracy toward excellent service that is more responsive, humane, and collaborative. Nevertheless, the implementation of this administrative transformation still faces several challenges, including limited disability-friendly technological infrastructure and the need to enhance the capacity of administrative human resources in managing digital-based inclusive education services. This study concludes that the modernization and efficiency of educational administration governance constitute a strategic foundation for the successful implementation of inclusive education at the elementary school level. Administrative transformation functions not only as a managerial instrument but also as an essential component in realizing equitable, adaptive, and student-centered educational services for all learners.